Expanding the Clinical and Genetic Spectra of Primary Immunodeficiency-Related Disorders With Clinical Exome Sequencing: Expected and Unexpected Findings - Rudilla, Francesc; Franco-Jarava, Clara; Martínez-Gallo, Mónica; Garcia-Prat, Marina; Martín-Nalda, Andrea; Rivière, Jacques; Aguiló-Cucurull, Aina; Mongay, Laura; Vidal, Francisco; Solanich, Xavier; Irastorza, Iñaki; Santos-Pérez, Juan Luis; et al. (Frontiers in Immunology, 2019)
Primary immunodeficiencies (PIDs) refer to a clinically, immunologically, and genetically heterogeneous group of over 350 disorders affecting development or function of the immune system. The increasing use of next-generation sequencing (NGS) technology has greatly facilitated identification of genetic defects in PID patients in daily clinical practice. Several NGS approaches are available, from the unbiased whole exome sequencing (WES) to specific gene panels. Here, we report on a 3-year experience with clinical exome sequencing (CES) for genetic diagnosis of PIDs. We used the TruSight One sequencing panel, which includes 4813 disease-associated genes, in 61 unrelated patients (pediatric and adults). The analysis was done in 2 steps: first, we focused on a virtual PID panel and then, we expanded the analysis to the remaining genes. A molecular diagnosis was achieved in 19 (31%) patients: 12 (20%) with mutations in genes included in the virtual PID panel and 7 (11%) with mutations in other genes. These latter cases provided interesting and somewhat unexpected findings that expand the clinical and genetic spectra of PID-related disorders, and are useful to consider in the differential diagnosis. We also discuss 5 patients (8%) with incomplete genotypes or variants of uncertain significance. Finally, we address the limitations of CES exemplified by 7 patients (11%) with negative results on CES who were later diagnosed by other approaches (more specific PID panels, WES, and comparative genomic hybridization array). In summary, the genetic diagnosis rate using CES was 31% (including a description of 12 novel mutations), which rose to 42% after including diagnoses achieved by later use of other techniques. The description of patients with mutations in genes not included in the PID classification illustrates the heterogeneity and complexity of PID-related disorders.